The overall motion sickness incidence applied to catamarans - Vincenzo Piscopo; Antonio Scamardella (International Journal of Naval Architecture and Ocean Engineering, 2015)
The Overall Motion Sickness Incidence is applied to the hull form optimization of a wave piercing high-speed catamaran vessel. Parametric hull modelling is applied to generate two families of derived hull forms, the former varying the prismatic coefficient and the position of longitudinal centre of buoyancy, the latter instead the demi-hull separation. Several heading angles are analysed in a seaway, considering all combinations of significant wave height and zero-crossing period under two operating scenarios. The optimum hull is generated and vertical accelerations at some critical points on main deck are compared with the parent ones. Finally a comparative analysis with the results obtained for a similarly sized monohull passenger ship is carried out, in order to quantify, by the OMSI, the relative goodness in terms of wellness onboard of monohulls and catamarans, as a function of sea states and operating scenarios.